Towards a multiscale modeling framework for metal-CNT interfaces - Claus, M.; Fediai, A.; Mothes, S.; Knoch, J.; Ryndyk, D.; Blawid, S.; Cuniberti, Gianaurelio (Giovanni); Schroter, M. (2014 International Workshop on Computational Electronics, IWCE 2014, 2014)
This paper gives a short overview on our recent investigations towards a multiscale modeling and simulation framework for metal-CNT interfaces. We employ three simulation approaches with well defined interfaces. For the simulation at device level we make use of a recently developed wave-function based effective-mass Schrȯdinger-Poisson solver which employs a hetero-junction like contact model to capture the physics in the contact region where the CNT is embedded into metal. The required model parameters are adjusted to TB and DFT simulation results. A comparison with experimental data for a short channel device shows the applicability of the proposed approach. © 2014 IEEE.
CRIS-Team Scopus Importer:2023-03-20